KAJIAN NORMATIF TERHADAP INVESTASI PERDAGANGAN KARBON DI INDONESIA DALAM REGULASI PENYELENGGARAAN NILAI EKONOMI KARBON (NEK) - Posma Sariguna Johnson Kennedy; anastasia (Fundamental Management Journal, 2024)
Climate change is an urgent global challenge, and one solution adopted by Indonesia is carbon trading. This study aims to examine the regulation aspects of carbon trading implementation in Indonesia, focusing on Presidential Regulation No. 98 of 2021 on Carbon Economic Value. The research uses a qualitative approach with normative study methods, involving literature analysis, documentation, and interviews. The findings indicate that clear regulations and inter-ministerial coordination are crucial to ensure that carbon trading is conducted transparently, fairly, and effectively. The implementation of this policy is expected to support climate change mitigation and adaptation as well as sustainable economic development in Indonesia. Keywords: Climate change, Carbon trading, Regulatory aspects, Indonesia.